Tongue function is important for masticatory performance in the healthy elderly: a cross-sectional survey of community-dwelling elderly. Issue 1 (January 2019) - Sagawa, Keiichiro; Furuya, Hiroyasu; Ohara, Yuki; Yoshida, Mitsuyoshi; Hirano, Hirohiko; Iijima, Katsuya; Kikutani, Takeshi
Abstract: Purpose: The aim of this study was to determine the influences of oral motor function such as tongue function and bite force on masticatory performance in the elderly. Methods: We randomly selected 245 subjects who has 28 natural teeth among community-dwelling elderly. We evaluated masticatory performance using a gummy jelly, and also measured bite force, tongue muscle force, and the speed of tongue movement. Results: We found that reduced masticatory performance to be associated with decreased the speed of tongue movement and/or tongue muscle force, indicating that reduced oral motor function also influences masticatory performance. Conclusions: These results suggest that keeping oral motor function, as well as maintenance of occlusal support, to be important for maintaining masticatory function in the elderly.